Where do measures of health, social care and wellbeing fit within a wider measurement framework? Implications for the measurement of quality of life and the identification of bolt-ons. (November 2022) - Finch, Aureliano Paolo; Mulhern, Brendan
Abstract: Background: There is variability across studies in the dimensionality i.e., set of latent variables to which health, social care and wellbeing measures relate. This variability may impact the development of new measures and the identification of bolt-on dimensions. We examine the dimensionality of commonly used measures and identify a set of potential bolt-ons for the EQ-5D-5L. Methods: We used the OMS dataset, an online survey of health, social care and wellbeing measures in patients and members of the general public. A content analysis provided a theoretical framework for results interpretation. Quantitative analyses were based on a pool of 79 items from 7 measures. Confirmatory factor analysis was used to assess health, social care and wellbeing measures dimensionality and their contribution to quality of life. The relationship between EQ-5D-5L items and the identified factors was used for bolt-ons identification. Results: The dimensionality comprised of seven factors, namely physical functioning, psychological symptoms, energy/sleep, physical pain, social functioning, needs and satisfaction. Health measures covered five of the seven factors identified, wellbeing measures three and the social care measure one. A list of candidate bolt-on items for the EQ-5D-5L was presented e.g., cognition, energy, dignity. Conclusions: This study provides evidence on the dimensionality of health, social care and wellbeing measures and presents a list of candidate bolt-ons for the EQ-5D-5L. Highlights: There is overlap in the mental aspect measured by HRQoL and mental WB measures. There is overlap in the aspect measured by capability WB and SCrQoL measures. Capability WB and subjective WB measure different aspects. HRQoL measures relate to physical, social and psychological aspects, sleep and pain. A list of candidate bolt-ons for the EQ-5D is provided.